Möbius Aromatic Core‐Modified Heterocyclic [20] Macrocycles (4.1.1) with a Protruding N‐Methyl Pyrrole Ring. Issue 7 (25th February 2016) - Mallick, Abhijit; Rath, Harapriya
Abstract: Herein, we report the first synthesis of an unorthodox tripyrrane moiety from the regioselective β‐benzoylation of pyrrole and the acid‐catalyzed condensation of the desired precursors. A [3+1] Mac Donald type condensation strategy for this tripyrrane has led to the exclusive isolation of two hitherto‐unknown aromatic [20] heterocyclic macrocycles (4.1.1). Abstract : Wow, [20]π Aromaticity ! Two core‐modified aromatic [20] heteroannulenes through the β–β connectivity of an N ‐methyl pyrrole ring have been isolated for the first time.